New insights into structural, electronic, reactivity, spectroscopic and pharmacological properties of Bergenin: Experimental, DFT calculations, MD and docking simulations - Costa, Renyer A.; da Silva, Jonathas N. [UNESP]; Oliveira, Viviane G.; Anselmo, Lucas M.; Araújo, Míriam M.; Oliveira, Kelson M.T.; Nunomura, Rita de Cássia S. (Elsevier, 2021)
Bergenin is a polyphenol found in many medicinal plants that presents numerous activities, such as antiulcer, anti-inflammatory, antifungal, anticancer, antimicrobial, antidiabetic, antiviral and antioxidant, being, therefore, a research target nowadays. In the present study, bergenin, isolated from Endopleura uchi Huber Cuatrecasas plant, was studied through density functional theory (DFT) and time-dependent density functional theory (TD-DFT), at the B3LYP/6–311++G(2d,2p) and B3LYP-D3(BJ)/6–311+G(2d,p) levels, where the obtained optimized geometry, FT-IR and UV–Vis data were analyzed along with experimental data. The comparative IR studies, together with potential energy distribution (PED) calculation, enabled the assignment of the observed experimental IR bands, besides evaluating the existence of intermolecular H-bonds through dimers formation. The calculated electronic transitions are in good agreement with the experimental data, which allowed the characterization of the UV–Vis bands. HOMO-LUMO energy gaps, average local ionization energy (ALIE) surfaces and Fukui indices calculations were carried out, allowing to concisely evaluate the reactive sites of bergenin. Also, calculations of solvation free energies and free energies of association in water, methanol and ethanol were performed. Due to the know in vitro anti-inflammatory and anticancer activities presented by bergenin, molecular docking and molecular dynamic (MD) calculations were carried out in front of cyclooxygenases 1 and 2 and topoisomerases I and II, revealing good interactions of bergenin with the active site of the tested enzymes, justifying the experimental results found in literature.
Keywords: Bergenin; COX 1 and 2; DFT; Molecular docking; Molecular dynamics; Topoisomerase I and II